Analisis Pengaruh Pemanfaatan Teknologi Informasi, Dukungan Manajemen Puncak dan Pengetahuan Manajer Terhadap Efektivitas Sistem Informasi Akuntansi di Fakultas Ekonomika dan Bisnis Universitas Diponegoro - Santoso, Budi; Luhgiatno, Luhgiatno; Wahyuningsih, Panca (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
The purpose of this study was to determine the effect of the use of information technology, top management support and manager's knowledge on the effectiveness of accounting information systems. This research was conducted at the Faculty of Economics and Business, Diponegoro University. The population in this study were employees of the Faculty of Economics and Business, Diponegoro University, totaling 158 people. The sample used in this study using purposive judgment sampling method. This sample uses certain considerations that are tailored to the research objectives or research problems developed, namely 88 employees who use the accounting information system. This study uses multiple regression analysis techniques. The results of testing the hypothesis of the effect of the variable use of work information technology on the effectiveness of the accounting information system are proven. it can be interpreted that the better the use of work information technology, the higher the effectiveness of the accounting information system. Hypothesis testing of the influence of work top management support variables on the effectiveness of accounting information systems is proven, so it can be interpreted that the higher the work top management support, the more effective the accounting information system is. Hypothesis testing of the influence of the manager's knowledge variable on the effectiveness of the accounting information system is proven, so it can be interpreted that the better the knowledge the manager is given, the more effective the accounting information system is.Keywords: Utilization of information technology, top manager support, manager's knowledge, effectiveness of accounting information systems